Productivity growth, convergence, and distribution dynamics in the Kansas farm sector - Mugera, Amin William (Kansas State University, 2009)
This study applies recent advances in nonparametric techniques to investigate growth in labor productivity and convergence in the Kansas farm sector for a panel of 564 farms for the period 1993-2007. The study seeks to answer two questions: First, what are the sources of labor productivity growth in the farm sector and second, is there evidence of convergence or divergence in the growth rate of labor productivity across farms? Following Kumar and Russell (2002), the nonparametric production frontier approach is used to decompose the growth in output per worker into three components: efficiency change, technical change, and capital deepening. Kernel density estimation methods are used to investigate the evolution of the entire distribution of labor productivity and the effects of each of those three growth components on the evolution of the distributions over the sample periods, 1993-07, 1993-02, and 1996-05. Cross-sectional regression methods (ordinary least square, partial linear model, and smooth coefficient model) are later employed to test for convergence in labor productivity growth and the contribution of each of the components to the convergence process. The study yields the following results. First, capital deepening and technical change are the main sources of labor productivity growth. Efficiency change is a source of regress in productivity growth. Second, technical change is not neutral. Third, the distribution of labor productivity in the farm sector has remained unimodal. Capital deepening and technical change are the main factors contributing to labor productivity distributions. Fourth, despite no evidence of technological catching-up, efficiency change and capital deepening contributed to convergence in the growth rate of labor productivity during the entire sample period. Technical change contributes to productivity disparity in the 1993-07 period. The contribution of technical change in the 1993-02 and 1996-05 periods are mixed with evidence of both convergence and disparity. Finally, the results for the 1993-07 period support the existence of a positive relationship between the annual growth in technical change and initial level of capital-labor ratio, suggesting that technology is embodied in capital accumulation.
Keywords: Labor productivity; Efficiency change; Technical change; Capital deepening; Convergence; Distribution dynamics; Agriculture, General (0473); Economics, Agricultural (0503); Economics, General (0501)